The Platformisation of Consumer Culture: A Digital Methods Guide - Alessandro Caliandro; Alessandro Gandini; Lucia Bainotti; Guido Anselmi (Amsterdam University Press, 2024)
This book offers a unique methodological guide for social and marketing scholars interested in understanding and using digital methods to explore the processes of platformisation of consumer culture unfolding on digital media. The book introduces the reader to key digital methods concepts, strategies, and techniques through a set of ad hoc case studies focused on the most prominent digital platforms (such as Facebook, Spotify, or TripAdvisor) as well as emerging trends in digital consumer culture (such as, the consumption of nostalgia, the radicalisation of taste, or ephemeral consumption).
Keywords: 650; digital methods; digital platforms; platformisation; consumer culture; marketing; social media